A home-based intervention towards preschoolers’ EFL sentence development - Ratnadewi, Dwijani; Wijaya, Armeria (JEES (Journal of English Educators Society), 2021)
Research has shown that the initial few years of children’s lives are the best times for language to develop at a rapid pace, the first language (L1) or a foreign language (FL) may be acquired these times. Researches on preschoolers FL acquisition with home-based intervention (HBI) have not been studied extensively under the L1 environment. This study aims to examine the results of HBI on the development of the acquisition of Indonesian preschoolers’ English as a Foreign Language (EFL) sentences. This research is a case study with naturalistic observation design, where data were obtained from logbooks and interview. The research subjects were 2 preschoolers about 36 months. The study’s duration was 24 months from the 13th until the 36th month with HBI, namely parents-based and authentic/semi authentic-media intervention. The data were the children’s English sentences taken at 24th to 36th months at their own homes. The Owens’ acquisition of sentence forms measured the English sentences’ development of in the respondents’ conversation and self-narration. This research found that at about 36th month, these Indonesian preschoolers were able to communicate in English in various sentences such as declarative, negative, interrogative, imperative, embedded and conjoining. HIGHLIGHTS: Simultaneous foreign language learning and first language acquisition for children is tangible advantage. Authentic input and active interaction act as the language environment substitute in foreign language learning. Intensive learning makes preschoolers speak a foreign language earlier.